A new species and additional records of the genus Collyria Schiødte, 1839 (Hymenoptera, Ichneumonidae) from Turkey - Yurtcan, Murat; Kolarov, Janko (Zootaxa, 2015)
A new species, Collyria pronotalis Yurtcan and Kolarov sp. n. (Hymenoptera, Ichneumonidae, Collyriinae), from Turkey is described and illustrated. A key for identification of the species of Collyria Schiødte, 1839 is provided. Moreover, additional records are reported for Collyria coxator (Villers, 1789) from Turkey.